THE IMPACT OF ENTREPRENEURIAL-ORIENTATION WORKING ENVIRONMENT ON EMPLOYEE WORKING ATTITUDE : CASE: SERVICE SECTOR IN VIET NAM - Vuong, Chau (My University, 2020)
This study provides more insights on the existing literature regarding Entrepreneurial – Orientation (EO) and employee attitudes. It focuses on evaluating the correlation between three dimensions of EO: innovativeness, risk-taking and proactiveness and two aspects of employee attitude: job satisfaction and organizational commitment. This empirical study was conducted in the context of service industry in Viet Nam by using data collected through 143 employees in Viet Nam. The results from analyzing the collected data revealed that innovativeness and proactiveness have significant positive impacts on employee attitude in both aspects. Especially, proactiveness shows the strongest influence on all facets of job satisfaction and organizational commitment. Risk-taking dimension shows no significant impact on both intrinsic satisfaction and organizational commitment. In developing country like Vietnam, extrinsic satisfaction shows the most impact on job satisfaction rather than intrinsic aspect. Likewise, some managerial implications are suggested to the managers of companies who would like to apply EO to enhance the employee’s attitude. This study based on the three-dimension of EO model introduced by Covin and Slevin (1989); the Job Diagnostic developed by Hackman and Oldham (1974); Job Descriptive Index invented by Spector (1985) and the three-component of organizational commitment developed Meyer, Allen, and Smith (1993) to build the theoretical background for this study. Then, a final framework has been presented to illustrate the impact of three dimensions of EO working environment namely innovativeness, risk-taking and proactiveness on employee attitude aspects namely job satisfaction and organizational commitment. In this framework, all three dimensions have positive relationship with of employee’s job satisfaction. However, only innovativeness and proactiveness have positive impact on organizational commitment of employees while risk-taking dimension has no relationship with this aspect of employee’s attitude.

Bài nghiên cứu này cung cấp nhiều giá trị học thuật cho các đề tài liên quan đến Định hướng sáng nghiệp và thái độ của nhân viên. Nó tập trung đánh giá mối quan hệ giữa ba yếu tố của EO gồm: sáng tạo, mạo hiểm, và chủ động và hai yếu tố đo lường thái độ nhân viên gồm: sự thỏa mãn trong công việc và sự gắn bó với công ty. Bài nghiên cứu được thực hiện dựa trên kết quả khảo sát của 143 nhân viên đang làm việc trong ngành dich vụ tại Việt Nam. Kết quả từ dữ liệu phân tích cho thấy sự sáng tạo và chủ động có tác động tích cực đến cả hai phương diện của thái độ nhan viên. Đặc biệt, sự chủ động có ảnh hưởng mạnh nhất đến tinh than của nhân viên. Trong khi yếu tố mạo hiểm không thể hiện tác động nào đến sự thỏa mãn từ yếu tố bên trong của nhân viên và sự gắn bó với tổ chức. Ở những nước đang phát triển như Việt Nam sự thỏa mãn về các yêu tố bên ngoài có ảnh hưởng nhiều hơn đến sự thỏa mãn chung của nhân viên. Từ đó, tác giả đưa ra một vài đề xuất cho ban quản lý công ty và các nhà làm chính sách khi áp dụng chiến lược Định hướng sáng nghiệp để nâng cao tinh thần làm việc của người lao động Bài nghiên cứu này dựa vào mô hình 3 yếu tố của Covin và Slevin (1989); mô hình Job Diagnos-tic của Hackman and Oldham (1974, 67); Job Descriptive Index của Spector (1985,708-711) và lý thuyết ba nhân tố gắn kết với tổ chức của Meyer, Allen, và Smith (1993) để xây dựng lý thuyết cho bài nghiên cứu này. Sau đó, một mô hình thể hiện sự tác động của ba khía cạnh của môi trường làm việc theo định hướng sáng nghiệp EO đến hai nhân tố của thái độ nhân viên gồm sự thoải mãn trong công việc và sự gắn bó với tổ chức. Trong mô hình này, cả ba khía cạnh của EO đều có tác động tích cực đến sự thỏa mãn trong công việc của nhân viên. Tuy nhiên, chỉ có khía cạnh sáng tạo và chủ động ảnh hưởng đến sự gắn bó với tổ chức trong khi sự mạo hiểm không có bất kì tác động nào đến sự gắn bó của nhân viên.
Keywords: Entrepreneurial-Orientation, job satisfaction, organizational commitment, developing country